Negrito culture, its implications for social studies materials - Laxamana, Jose C. 1930-
This study is a field investigation of the Negrito culture in Western Capas, Tarlac which aimed to determine their political life, economic life, socio-cultural and traditional practices, their attitudes towards the government and the cultural plurality, and their education and problems. Participant observation was used. A Negrito guide-translator was employed to guide the researcher in the various villages and to translate for him a few Negrito terms into Pampango. The respondents were the datu and four married men or women of an ethnic village and the datu and four married men or women of another village. It was concluded that the Negritos views and practices are important sources of knowledge for social studies materials in the elementary and secondary schools.